Rome Оut of Borders: The French Architects in Rome in the Middle of the 16th Century - Efimova, Elena A. (Actual Problems of Theory and History of Art, 2019)
The article focuses on the studies of Rome ancient monuments carried out by French architectsin Rome in the period of the 1530–1550s. This activity has got a scarce record in historical documents, with the exception of Philibert Delorme’s treatise, which contains valuable information about the interests of its author, his contacts in Italian intellectual circles, his method of selecting and studying monuments, as well as the way of managing the teams of architects engaged in excavations and measurements of antiquities. Since other written sources shed no light on French masters, the main source of information can be found in the albums of drawings made in Rome and devoted to the study of ancient architecture. They form a sizeable array, comprising several large albums stored in the Kunstbibliothek in Berlin, the Metropolitan Museum in New York, the Nationalmuseum in Stockholm and the Bavarian State Library in Munich — with total volume exceeding 500 sheets. The studies of recent years carried out by Bernd Kulawik allowed him to put forward a hypothesis about single origin of this entire archive as well as its connection to the research project of the Accademia della Virtù Claudio Tolomei run in the mid of 1540s in the context of preparing a complete topographical plan of ancient Rome with the reconstruction of all major monuments. The article aims to test this hypothesis by examining connections and correlations between the albums. Though the author has not found convincing evidence for the hypothesis of a single origin of the archive, she may see a unified method of studying and representing the ancient monuments. She believes this may be based on the connection between the authors of the archive and the St. Peter’s workshop, which ensured the continuity in the way of studying and representing the antiquities.
Keywords: studies of antique monuments; architectural drawings; measurements; albums of drawings; Philibert De l’Orme; Jean Bullant; Guillaume Philandrier; Accademia della Virtù; Accademia Vitruviana; Claudio Tolomei; St. Peter’s workshop